AN ANALYSIS OF GENDER DIFFERENTIATION AND HOW IT CREATES GENDER PAY GAP IN CORPORATION (CASE STUDY AT PT. TIGA DIMENSI DATA) (The Indonesian Journal of Business Administration, 2019)
The focus of this research is to analyze the cause of gender pay gap issues and how it affect the workforce, especially women workers. The research method in this study is a combination of qualitative and quantitative research, by adopting one method, it is case study. The researcher use the case study method due to analyze the gender pay gap that occurs in one of the industrial manufacturing company, PT. Tiga Dimensi Data.The data obtained from the company were analyzed and showed the cause of the gender pay gap was due to first, occupational sexism in the form of gender stereotypes carried out by managers and company directors, restrictions on employment opportunities and women's rights, and second, occupational segregation in both of horizontal and vertical. One interesting findings that was discovered by researchers was the “acceptance” of female employees who consciously know that their wages were being given unfairly.The research concluded that the analysis of gender differences had an impact on the existence of gaps and differences in pays between male workers and female workers in PT. Tiga Dimensi Data.Keywords: Gender pay gap, women labor, gender role, occupational sexism, occupational segregation